Network Pharmacology and Molecular Docking Analysis on Molecular Mechanism of Qingzi Zhitong Decoction in the Treatment of Ulcerative Colitis - Shou, Xintian; Wang, Yumeng; Zhang, Xuesong; Zhang, Yanju; Yang, Yan; Duan, Chenglin; Yang, Yihan; Jia, Qiulei; Yuan, Guozhen; Shi, Jingjing; Shi, Shuqing; Cui, Hanming; et al. (Frontiers in Pharmacology, 2022)
Ulcerative colitis (UC) is a disease with complex pathological mechanisms. We explored the potential molecular mechanisms behind the therapeutic functions of Qingzi Zhitong Decoction (QZZTD) in the treatment of UC by network pharmacology and molecular docking. QZZTD is a formula of Chinese traditional medicine consisted of 10 herbs. The potential active ingredients of QZZTD and their target genes were obtained from the Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform database, and UC-related target genes were obtained from the GeenCards and OMIM databases. A total of 138 co-identified target genes were obtained by plotting the intersection target Venn diagram, and then the STRING database and Cytoscape software were used to establish protein-protein interaction networks and herb-ingredient-target networks. Four key active compounds and nine key proteins were identified. Then Gene Ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses showed that the biological functions of potential target genes were associated with DNA transcription, signaling receptor and ligand activity, cytokine activity, cellular autophagy, and antioxidant pathways, with related pathways involving Phosphatidylinositol 3-kinase (PI3K)-Akt signaling pathway, the advanced glycosylation end product (AGE)-RAGE signaling pathway, tumor necrosis factor (TNF) signaling pathway, and IL-17 signaling pathway. Moreover, the binding activities of key target genes and essential active compounds of Chinese herbal medicines in QZZTD were further validated by molecular docking. This demonstrated that quercetin, luteolin, hyndarin, and beta-sitosterol had good binding to eight key proteins, and Akt1 was the target protein with the best binding activity, suggesting that Akt1 could be the essential mediator responsible for signaling transduction after QZZTD administration. The rat experiment verified that QZZTD inhibited PI3K-AKt pathway activation, reduced inflammation in UC. In conclusion, our study suggested four potential key active components, such as quercetin, were identified in QZZTD, which could interact with Akt1 and modulate the activation of the PI3K-Akt pathway. The other three pathways may also be involved in the signaling transduction induced by QZZTD in the treatment of UC.